Probing Proton Coupled Electron Transfer and Fluorine Atom Transfer in CoII-Catalyzed Oxidative Hydrocarbon Fluorination - McDonald, Aidan (My University, 2025)
In exploring CoII-catalyzed oxidative fluorination, we have synthesized a family of CoII complexes supported by linear tetradentate ligands. Nuclear magnetic resonance and infra-red spectroscopies, mass spectrometry, and X-ray crystallography provided insights into the structural and electronic properties of the catalysts. All complexes displayed a cis- geometry at Co, while displaying variable CoII/III E1/2 values. Certain catalysts delivered near quantitative yields of fluorinated product in the selectfluor-mediated fluorination of 1-adamantanol. The rate of fluorination was impacted by the nature of the supporting ligands, with more electronic-rich Co sites displaying faster rates of fluorination, but lower yields of fluorinated product. Kinetic analysis suggested that proton coupled electron transfer (PCET) C–H activation was rate-limiting (substrate kinetic isotope effects = 2). We concluded that a CoIV(F)2 entity was the likely PCET oxidant producing an alkyl radical, HF, and CoIII–F. In order to explore how the alkyl radical and CoIII–F reacted through fluorine atom transfer (FAT), we probed a series of radical clock bicyclic substrates in the CoII-catalyzed reaction. Product analysis supported the occurrence of a fast FAT rebound, consistent with the alkyl radical being in close proximity to the fluorine donor.
PUBLISHED
Keywords: FLUORINE; Kinetic isotope effect; OXIDATIVE ADDITION; Proton-Coupled Electron Transfer